Optimization of Hajj and Umrah Services: Strategic Management of Semarang Islamic Center Hajj Dormitory - Wahid Akbar Ismuhadi Harahap; Anasom (International Journal of Economics Development Research (IJEDR), 2023)
Hajj and Umrah are one of the pillars of Islam that must be carried out by Muslims who have met the requirements. Semarang Islamic Center Hajj Dormitory is one of the transit dormitories in Indonesia, especially Central Java. This study aims to evaluate the strategic management of the Semarang Islamic Centre Hajj Dormitory in optimizing the services of Hajj and Umrah pilgrims. This dormitory will be used for the first time in the 2023 Hajj season. The research method used is qualitative with a descriptive approach. The data collection techniques used are interviews, observation, and documentation. The results showed that the Hajj Dormitory has formulated a clear strategy, established cooperation, and conducted certification and training for staff. The Hajj Dormitory is supervised by the Regional Office of the Ministry of Religious Affairs of Central Java and periodic monitoring is carried out. There are still obstacles in services, such as lack of human resources, facilities and infrastructure, coordination between related institutions, and congestion during the return of pilgrims. Based on the results of the research, several things are recommended to optimize the services of Hajj and Umrah pilgrims at the Islamic Centre Semarang Hajj Dormitory, including improving the quality and quantity of human resources, completing the facilities and infrastructure of the Hajj dormitory, and improving coordination between related institutions. By continuing to evaluate and improve, the Islamic Center Semarang Hajj Dormitory is expected to become a quality embarkation Hajj dormitory and provide the best service for Hajj and Umrah pilgrims.